2002
DOI: 10.1016/s0893-133x(01)00344-x
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Monoamine Correlates of Social Dominance in Cynomolgus Monkeys (Macaca fascicularis)

Abstract: Social dominance is a fundamental component of both human and nonhuman primate sociality. However, its neurobiological correlates remain incompletely understood. We evaluated the association between dominance status and monoamine metabolite concentrations in cisternal cerebrospinal fluid (CSF) in adult male (n ϭ 25) and female (n ϭ 21) cynomolgus macaques ( Macaca fascicularis ) housed in unisexual social groups. Concentrations of the metabolites of dopamine (homovanillic acid [HVA]), norepinephrine ) and sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 58 publications
(90 reference statements)
1
74
4
Order By: Relevance
“…There is unequivocal evidence that social status exerts a profound impact on nonhuman primate physiology (e.g., Grant et al, 1998;Kaplan and Manuck, 1999;Kaplan et al, 2002) and can influence the behavioral effects of dopaminergic drugs. For example, effects of d-amphetamine on aggression are more profound in dominant than subordinate squirrel monkeys (Miczek and Gold, 1983;Martin et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…There is unequivocal evidence that social status exerts a profound impact on nonhuman primate physiology (e.g., Grant et al, 1998;Kaplan and Manuck, 1999;Kaplan et al, 2002) and can influence the behavioral effects of dopaminergic drugs. For example, effects of d-amphetamine on aggression are more profound in dominant than subordinate squirrel monkeys (Miczek and Gold, 1983;Martin et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, animal studies have found that the creation of hierarchies affects activity in dopaminergic pathways of the brain associated with motivation (e.g., Kaplan et al 2002, Morgan et al 2002. For instance, Morgan et al (2002) first housed monkeys individually and found that they had similar dopamine levels.…”
Section: Power As Activating Wanting and Goal Seeking: Empirical Evmentioning
confidence: 99%
“…Thus, while there are few changes in brain serotonergic activity following a second interaction with a familiar opponent, those that occur do not appear to be increases stimulated by a second stressful social interaction, but rather are represented by reductions in serotonergic activity, modulated by visual sign stimuli (raphé) and previous social status (hippocampal CA 3 ) respectively [39]. Dopaminergic activity is also influenced by social status and social interactions [3,17,32,51,84]. Dopaminergic activity in hippocampal nuclei of various vertebrate species has also been shown to be critical for spatial memory formation and retrieval [61,81].…”
Section: Central Monoaminergic Response To a Second Social Interactionmentioning
confidence: 99%